Combined glycerol and sodium bicarbonate elicits improvements in fluid retention and blood buffering capacity - Ben Patrick; Charles Urwin; Andrew C. Betik; William T. Jardine; Rhiannon Snipe; Monica Kelly; D. Lee Hamilton; Amelia Carr (PLoS ONE, 2026)
Introduction Background: It is unclear whether hyperhydration induced via glycerol, sodium bicarbonate or a combination of the two is most effective. Aim: This study evaluated the effects of glycerol-, sodium bicarbonate-, and glycerol + sodium bicarbonate-induced hyperhydration on measures of fluid retention, blood buffering capacity, and gastrointestinal symptoms at rest, in comparison to a fluid-only control. Methods Eleven healthy participants (six male) completed four trials (randomised, crossover design). Treatments consisted of glycerol-(G) = 1.0 g·kg -1 body mass glycerol; sodium bicarbonate-(SB) = 0.3 g·kg -1 body mass sodium bicarbonate; and combined glycerol and sodium bicarbonate supplementation-(G + SB) = 1.0 g·kg -1 body mass glycerol + 0.3 g·kg -1 body mass sodium bicarbonate; and a fluid only control-(CON) = 25 mL·kg -1 body mass artificially sweetened water. At baseline and at 20 min intervals for 180 min, urine samples were collected and analysed for volume, colour, and specific gravity, and gastrointestinal symptoms and body mass were quantified. At 60 min intervals, capillary blood was analysed for pH, blood bicarbonate concentration and plasma volume change. Results Compared to CON, fluid retention was significantly higher with G + SB from 120–180 min, SB from 120–140 min, and G from 160–180 min (p < 0.05), and accumulated urine volume was significantly lower with G + SB from 100–180 min, SB from 120–180 min, and G from 140–180 min (p < 0.05). There were no significant differences in fluid retention between G + SB, SB or G at any time point (p > 0.05). Compared to G and CON, blood pH and blood bicarbonate concentration was significantly higher with G + SB and SB from 60–180 min (p < 0.05). Conclusions Fluid retention improved in G, SB and G + SB compared to CON, although there were no additive effects with G + SB compared to SB or G. Buffering capacity was significantly higher with SB and G + SB compared to G and CON. Minimal GI symptoms were induced by G, SB, G + SB and CON.